Responding to English Grammatical Challenges: The Design and Development of Exemplary Material for Form One Learners in Tanzania - Fancis William; Gilbrita John Hamaro (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2018)
This article proposes strategies for designing and evaluating curriculum materials for enhancing English language grammatical competence among Form One learners in Tanzanian secondary schools. Using quasi-experimental and phenomenological designs, the authors developed an exemplary Learner Centered Instructional Grammar Material (LCIGM) focusing on Form One learners. Materials design approach and Constructivism Theory of learning guided the exercise. The data for the study were collected through documentary review, interviews, questionnaires and teaching and learning observations of 40 Form One learners chosen from three randomly selected secondary schools in the Dodoma Region of Tanzania. Both pre-test and post-tests were done to understand the suitability of the newly developed material to meet the purpose of enhancing grammatical competence among Form One learners. The findings and observations revealed that both teachers and learners benefited from the designed activity-based material which, in turn, enhanced learners' grammatical performance, both in spoken and written form. The authors concluded by urging the stakeholders to design the material that are activity based to improve the learners' grammatical competence.